Milkfish (Chanos chanos Forskal) Traditional Pond Stability Based On Water Quality Analyses And Periphyton Availability - Sulastri Arsad; Luthfiana Aprilianita Sari; Muhammad Zainuddin; Muhammad Musa (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
Milkfish is potential fish with high production and belong to ten of fish commodities culture in Indonesia. Pond stability of milkfish especially in fingerling phase (young phase) influenced by several factors including water quality and organism availability (periphyton). This recent study aimed to assess the milkfish traditional pond stability in fingerling phase based on water quality and periphyton availability aspects. These aspects are quite important to milkfish production and their growth as well as their food habit. The research was conducted in traditional pond located in UPT Fisheries Brackish and Saline Water Probolinggo for three months. Water quality and periphyton analyses were in situ and ex situ. The result shows that all the water quality is belong to good condition (stable) except in ammonia, TOM, and orthophosphate. However, this fluctuated value is not significantly impacting to the living organisms (milkfish). The research concluded that the fingerling milkfish traditional pond is belonging to moderate to stable condition.